Dividend policy of companies listed on European and American capital markets – comparative analysis - Jabłoński, Bartłomiej; Kuczowic, Jacek (Polityka dywidend spółek na europejskich i amerykańskich rynkach kapitałowych – analiza porównawcza, 2016)
This paper discusses the issue of the dividend distribution from the perspective of capital market investors and dividend distributing companies, listed on the largest stock exchanges. The goal of the study is to demonstrate the specificity of the dividend policy of companies functioning on the world’s most developed capital markets – the USA and Western Europe. The study covers 150 companies, their dividend policy, as well as the regularity and dynamics of dividend distribution in the period 2011-2015. The results of the study indicate that in companies listed on the developed capital markets, systematic dividend distribution constitutes a stable element of remunerating investors. The analysis also pointed to the considerable differences between the dividend policy adopted by companies listed on the Warsaw Stock Exchange and the dividend policy of companies which are components of the S&P500, FTSE100, DAX, and CAC40 indices
Nauki o Finansach = Financial Sciences, 2016, Nr 4 (29), s. 35-48
Keywords: dividend policy; dividend; investments; capital markets; polityka dywidend; dywidenda; inwestycje; rynki kapitałowe